THU0130 Improvement in measures of depressed mood and anhedonia in two randomized, placebo-controlled phase iii studies of sirukumab, a human anti-interleukin-6 antibody, in patients with rheumatoid arthritis. (15th June 2017) - Sun, Y; Hsu, B; Wang, D; Curran, M; Drevets, WC; Chen, G; Wittenberg, GM
Abstract : Background: Interleukin-6 (IL-6) is one of the known neuroactive-cytokines involved in neuronal plasticity and stress coping and is associated with depression. Depressive symptoms are common in patients with rheumatoid arthritis (RA), a disease characterized by high peripheral IL-6. Previous analysis of a Phase II study 1 showed that sirukumab, a human monoclonal antibody that selectively binds to the IL-6 cytokine with high affinity, can help reduce depressive symptoms in RA patients. Objectives: To further assess and validate the effects of sirukumab on relieving depressive symptoms in RA patients. Methods: We conducted a post-hoc analysis of 2 Phase III, randomized, double-blind, placebo-controlled trials evaluating efficacy and safety of sirukumab in the treatment of RA. SIRROUND-D enrolled patients with active RA despite disease-modifying anti-rheumatic drugs and having serum C-reactive protein (CRP)≥8mg/L at baseline. SIRROUND-T enrolled patients with active RA despite anti-TNF therapy and having serum CRP≥8mg/L or erythrocyte sedimentation rate≥28mm/h at baseline. Patients using antidepressants were excluded from the analysis. Patients were grouped by presence/absence of prevalent depressed mood and anhedonia (PDMA), based on the self-reported frequencies of these 2 core depressive symptoms in the SF-36, requiring one present at least "most of the time" and the other "some of the time" in the past 4 weeks. A depression score was derived based on the 2 core depressive symptoms of SF-36. Relief of depressive symptoms in patients with PDMA was evaluated by comparing changes in the depression score from baseline to week 8 between the placebo and combined sirukumab groups directly and with adjustment for RA activity as measured by the Disease Activity Score-28 with CRP. Changes in depression score were also analyzed in RA patients who did not have an ACR50 response to sirukumab. The combined effect of anti-IL-6 treatment was estimated using meta-analysis of 2 Phase III, 1 Phase II studies of sirukumab and 1 Phase II study of the anti-IL-6 cytokine antibody siltuximab. Results: At baseline, 19% and 22% of patients were classified as PDMA in the 2 studies, respectively. Sirukumab treatment, compared to placebo, significantly improved depressive symptoms by week 8 among PDMA patients (p=0.022 and 0.046 for the 2 studies, respectively) before adjusting for changes in RA activity. Within the sirukumab group, the reduction in depressive symptoms remained significant after adjusting for changes in RA activity (p<0.0001) and in ACR50 non-responders at week 8 (p<0.0001), while differences in improvements between the sirukumab and placebo group reduced to trends. Meta-analysis of 4 anti-IL-6 studies (1 siltuximab, 3 sirukumab) revealed that anti-IL-6 treatment helps alleviate depressive symptoms even after adjusting for changes in disease activity (Standardized Mean Difference =0.25, p=0.03). Conclusions: Our findings are consistent with previous results from a phase II RA study. Peripheral anti-IL-6 cytokine treatment is associated with improvement in depressive symptoms in RA patients, possibly supporting a role for IL-6 dysfunction in depression. References: Ann Rheum Dis2015;74(Suppl2): 720. Disclosure of Interest: Y. Sun Shareholder of: Johnson & Johnson, Employee of: Janssen Research & Develoment, LLC, B. Hsu Shareholder of: Johnson & Johnson, Employee of: Janssen Research & Develoment, LLC, D. Wang Shareholder of: Johnson & Johnson, Employee of: Janssen Research & Develoment, LLC, M. Curran Shareholder of: Johnson & Johnson, Employee of: Janssen Research & Develoment, LLC, W. Drevets: None declared, G. Chen: None declared, G. Wittenberg: None declared